Digital Surface Model (DSM) Construction and Flood Hazard Simulation for Development Plans in Naga City, Philippines - Abd Rahman, Muhammad Zulkarnain; Dinand, Alkema (2007)
A 2D-hydraulic flood propagation models require accurate elevation data. One of the main problems is frequent changes of land use in major cities, where frequent updating of the digital terrain model (DTM) for flood modelling might be needed. On the other hand the assessment should be based on realistic flood hazard indicator that would help to reflect the real impact of urban development on the surrounding areas. This paper presents an example of assessing the impact of flood for future developments in Naga City, the Philippines. The elevation data is constructed through integrating various elevation data derived from many sources. The development impact assessment begins with the detailed observation on changes in flood characteristics. This is supported by the analyses on the community-based flood risk perception and investigation on changes of flood hazard (based on the flood velocity and depth). In the DTM construction the natural terrain is separated from the man-made terrain. The geostatistical approach is used to investigate the effect of integrating multi-sources of elevation data by evaluating the nugget values. The data sources are prioritized based on the nominal horizontal and vertical accuracy, and form of data. In this paper, there are 4 interpolation methods used, namely Australian National University's Digital Elevation Model algorithm (ANUDEM), Kriging, Polynomial and Triangulated Irregular Network (TIN). The assessments are based on percentile vertical accuracy assessment, error point’s distribution and visual assessment. As a result, the kriging interpolation method has produced the best DTM and it full-filled the requirements for hydrological flood modelling purpose. Finally the Digital Surface Model (DSM) of the study area was constructed by integrating both man-made and natural terrains. The DSM was also generated to simulate the new developments in Naga City. The 1D2D SOBEK flood model was used to simulate flood events for 2, 5, 10 and 17.5 years return period flood. In addition, the flood depths and flood extent during Supertyphoon Nanmadol were used in flood model calibration. Flood calibration results revealed that the calibrated flood model was able to simulate the real flood event up to 0.35 m accuracy of flood depth. In the development impact assessment, it was found that the impact of the developments is larger for a larger flood magnitude. Furthermore the pattern of the changes in flood behaviour depends on the location from the main developments. The Almeda Highway acted as a barrier, that obstructs the flood water from go farther. In addition the small scale construction, for instance the Drainage System in Barangay Triangulo had played a major role in changing the flood behaviour, especially in a small magnitude flood. Through this study, it was proved that by simply elevating ground terrain only can solve the flood problem in a particular area. However, the flood problem is transferred to another area.